Common Pronunciation Errors Made by Students of English Language and Literature Department at Universitas Negeri Padang - Febrice Yumiza; Sitti Fatimah (Journal of English Language Teaching, 2022)
This  study was aimed to find empirical evidence of student errors in pronouncing segmental features of English language students in the 5th semester Universitas Negeri Padang. This research is a qualitative descriptive research. The subjects of this study were students in education class, international class and literature class who were taking speaking classes at Universitas Negeri Padang. while the object of this research is errors pronunciation in  segmental features of English Department. Then, to collect data, the researcher conducted interviews as an instrument to find errors. Interviews were conducted in the form of voice recordings by phone calling. Based on data analysis, the researcher found that some sounds that are often mispronounced are [ð], [θ], [k], [ʒ], [tʃ ], [ɔ:], and [ʊ]. All these errors make up almost 70% of the data. The single largest error occurred in [ð] and the occurrence was 76 times which the errors was 18% and the other largest error occurred in [θ] where the frequency about 59 times which the total errors counted 14% .then the sounds [k], [ʒ], [tʃ], [ɔ:], and [ʊ] have a relatively smaller error rate, namely 9%, 8%,8%, 7%. , and 6% respectively. In conclusion, from 30 students, it was found that there were a total of 423 errors made by students. Consonant errors are more obvious than vowel errors. The consonant error frequency is 293 which is more than 69% of the total errors, and the vowel error is 132 which is almost 31% of the errors.